2014
DOI: 10.1017/sjp.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

Rasch-Master’s Partial Credit Model in the Assessment of Children’s Creativity in Drawings

Abstract: Abstract. The purpose of the present study was to use the Partial Credit Model to study the factors of the Test of Creativity in Children and identify which characteristics of the creative person would be more effective to differentiate subjects according to their ability level. A sample of 1426 students from first to eighth grades answered the instrument. The Partial Credits model was used to estimate the ability of the subjects and item difficulties on a common scale for each of the four factors, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(48 reference statements)
1
1
0
1
Order By: Relevance
“…This analysis found that the observed 4-point scale ranged from a low of -2.34 to a high of 2.34 (4.68 logits) on a latent metric identifying meaningful points of the latent trait. Construct maps of creativity tests (Nakano & Primi, 2014) have demonstrated, as expected, that highly creative responses are rare. Consistent with this finding, the construct map of the MCT shows that people whose majority of metaphors exhibits remote associations (score > 2) are uncommon.…”
Section: Discussionsupporting
confidence: 68%
“…This analysis found that the observed 4-point scale ranged from a low of -2.34 to a high of 2.34 (4.68 logits) on a latent metric identifying meaningful points of the latent trait. Construct maps of creativity tests (Nakano & Primi, 2014) have demonstrated, as expected, that highly creative responses are rare. Consistent with this finding, the construct map of the MCT shows that people whose majority of metaphors exhibits remote associations (score > 2) are uncommon.…”
Section: Discussionsupporting
confidence: 68%
“…Las principales contribuciones a la evaluación del aprendizaje de la aplicación de la Teoría de respuestas al Ítem (TRI) se refieren a la posibilidad de su uso para medir el nivel de habilidad que tiene una persona con relación a cada elemento o característica de la competencia que se desea medir (Nakano y Primi, 2014). La TRI, además, permite analizar de manera detallada la estructura interna de los ítems que se utilizan para evaluar un área de competencia (como es el caso de las matemáticas), indicando cuáles de ellos exigen una menor o mayor capacidad por parte del estudiante.…”
Section: Modelo De Crédito Parcial De Rasch Y Mastersunclassified
“…Nakano and Primi () performed a factor analysis of this test in a sample of students from grades 1–8 ( n = 1,253) and found a four‐factor solution: enrichment of ideas, emotion, cognitive aspects, and creative preparation. They later used a Partial Credit Model to rank the difficulty of the 12 characteristics of creativity assessed by this test in a sample of 1,426 grade 1–8 students (Nakano & Primi, ). In their proposed hierarchy of difficulty, they found that unusual perspective, expression of emotion and originality required greater ability.…”
Section: Individual Differences In Creativitymentioning
confidence: 99%